Investigating the Effect of an Oxytetracycline Treatment on the Gut Microbiome and Antimicrobial Resistance Gene Dynamics in Nile Tilapia (Oreochromis niloticus) - Christopher J. Payne; James F. Turnbull; Simon MacKenzie; Margaret Crumlish (MDPI AG, 2021)
Antibiotics play a vital role in aquaculture where they are commonly used to treat bacterial diseases. However, the impact of antibiotic treatment on the gut microbiome and the development of antimicrobial resistance in Nile tilapia (Oreochromis niloticus) over time remains to be fully understood. In this study, fish were fed a single treatment of oxytetracycline (100 mg/kg/day) for eight days, followed by a 14-day withdrawal period. Changes in the distal gut microbiome were measured using 16S rRNA sequencing. In addition, the abundance of antimicrobial resistance genes was quantified using real-time qPCR methods. Overall, the gut microbiome community diversity and structure of Nile tilapia was resilient to oxytetracycline treatment. However, antibiotic treatment was associated with an enrichment in Plesiomonas, accompanied by a decline in other bacteria taxa. Oxytetracycline treatment increased the proportion of tetA in the distal gut of fish and tank biofilms of the treated group. Furthermore, the abundance of tetA along with other tetracycline resistance genes was strongly correlated with a number of microbiome members, including Plesiomonas. The findings from this study demonstrate that antibiotic treatment can exert selective pressures on the gut microbiome of fish in favour of resistant populations, which may have long-term impacts on fish health.